2019
DOI: 10.46223/hcmcoujs.soci.en.9.2.266.2019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of grouping types on promoting critical thinking in EFL collaborative writing

Abstract: Nurturing critical thinking (CT) has been acknowledged as a core objective of tertiary education, and drawn attention from academia of teaching English as a Foreign Language (EFL), particularly in EFL argumentative writing. It has been claimed that collaborative learning which stimulates the active exchange of ideas within small groups not only increases interest among the participants but also promotes critical thinking. One of the important aspects of learning and teaching through collaboration is the group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…When designing collaborative activities, one critical issue to address is group composition. There are studies that explore the differences between homogeneous and heterogeneous groups under several perspectives (e.g., [13,[37][38][39]). Some studies have suggested that homogeneous groups are effective to promote differentiated instruction (e.g., [40]); and that they can enhance engagement, especially in lower-achieving students (e.g., [13]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When designing collaborative activities, one critical issue to address is group composition. There are studies that explore the differences between homogeneous and heterogeneous groups under several perspectives (e.g., [13,[37][38][39]). Some studies have suggested that homogeneous groups are effective to promote differentiated instruction (e.g., [40]); and that they can enhance engagement, especially in lower-achieving students (e.g., [13]).…”
mentioning
confidence: 99%
“…Some studies have suggested that homogeneous groups are effective to promote differentiated instruction (e.g., [40]); and that they can enhance engagement, especially in lower-achieving students (e.g., [13]). On the other hand, a consistent body of research supports the use of heterogeneous grouping to enhance learning, since the lower-achieving students can learn from the higher-achieving ones [37][38][39]. However, many studies cannot find any difference between homogeneous and heterogeneous grouping, but that in both cases collaborative learning helps low-ability students more [41,42].…”
mentioning
confidence: 99%